ANALISIS PENGARUH JOB STRESS TERHADAP JOB BURNOUT: SLEEP DISTURBANCE SEBAGAI VARIABLE MEDIASI - Radiatul Husna; Stevany Stevany; Zaitul Zaitul; Listiana Sri Mulatsih (Universitas Bina Taruna Gorontalo, 2024)
This study aimed to determine the effect of job stress on job burnout. Besides this study also investigates the role of sleep disturbance as a mediating variable between job stress and job burnout. Four hypotheses were developed and tested using a quantitative approach. Research data is a hundred primary collected using survey methods. Variables are measured using a Likert scale of five with a range of very disagree (1) to very agree (5). The data analysing method employed a structural equation model (SEM) using Smart-Partial Least Square (PLS) 3.0 software. A measurement model and structural model assessment are used to obtain research results. After passing the evaluation of the measurement model, the structural model shows that the model has good predictive relevance and power. The result indicates that sleep disturbance mediates the relationship between job stress and job burnout (indirect-only mediation). Hence, the direct relationship suggests two significant relationships: (i) job stress and sleep disturbance and (ii) sleep disturbance and job burnout.